Effect of Esterification on Cassava Starch: Physicochemical Properties and Expansion Ability - Siswo Sumardiono; Listiyana Riska; Bakti Jos; Isti Pudjiastuti (Reaktor, 2019)
In this study, the characteristic of cassava starch have been developed through esterification reaction using ethyl lactate. Commercial cassava starch was modified by using (0.5; 0.75; 1.00; 1.25; 1.50 % v/v) ethyl lactate solution with pH 6, 7, 8, 9 for 15, 25, 35, 45, 55 minutes and the drained starch was dried with sun drying. The cassava starch which has been esterified with 1.5% ethyl lactate for 15 minutes pH 6 gave highest volume expansion of 2,438.9 %. For swelling power, the highest value was 19.32 swelling power at variable concentrations of 1.5% ester, esterification period of 15 minutes, and pH 6. The lowest amylose content was 15.68 % in ester concentration of 1.5 %. From the scanning electron micrograph, shows that the cassava starch after and before modification has not changed since the modifications performed under the gelatinization temperature. FTIR spectra of native cassava starch and ester cassava starch shown shift of the carboxyl group of starch from 1072.37 to 1087.80 cm-1 and a decrease in the OH group is from 3452.53 to 3417.81 cm-1. Bond formed indicates that the esterification reaction occurs between cassava starch with ethyl lactate esters. Keywords: volume expansion, cassava starch, ester starch, ethyle lactate, modified starch